In inpatient substance use disorder treatment in Switzerland, exercise programmes are implemented but not evaluated – A missed opportunity for improving treatment. (October 2018) - Colledge, Flora; Brand, Serge; Pühse, Uwe; Holsboer-Trachsler, Edith; Gerber, Markus
Abstract: Background: Although there is promising evidence for exercise and sport as an adjunct treatment in substance use disorders, to date there is little information about whether it is integrated into current clinical practice. Methods: 79 inpatient clinics in Switzerland were invited to take part in a telephone survey regarding exercise and sport programmes. Results: 46 clinics participated in the survey. 42 (91.3%) offer some type of exercise programme. Participation in at least one session per week was obligatory in 29 (63%) of clinics. None of these clinics evaluate the effects of participation. 4 clinics (8.7%) do not offer an exercise and sport programme; in one of these, the programme was stopped due to lack of patient interest; one was in the process of developing a programme; and two stated that their residents' health was too poor. Conclusion: Exercise and sport programmes are integrated into the treatment plans of at least half of the identified inpatient substance use disorder treatment clinics in Switzerland; however, while participation in these programmes is often compulsory, their effects are not evaluated. There is an urgent need to develop an evaluation process for the potential effects of exercise participation on substance use-related outcomes. Highlights: Little information about whether exercise is integrated into current substance abuse treatment is available. This study presents the results of a survey on exercise programmes in 46 inpatient substance use disorder clinics. While over 90% of responding clinics offer an exercise and sport programme, no evaluation takes places. To provide a sound evidence basis for exercise as an adjunct treatment, current practices must be assessed and evaluated.